Changes in Patellofemoral Joint Morphology During Skeletal Growth and Maturation are not Sex-Dependent. Issue 5 (31st May 2022) - Pruneski, James A.; Hosseinzadeh, Shayan; Emami, Seyed A.; Sanborn, Ryan; Barnett, Samuel; Kiapour, Ata M.
Background: Patellofemoral disorders account for approximately 25% of patients seen in sports medicine clinics. A variety of anatomic risk factors have been identified in the pathogenesis of patellofemoral instability. While studies have analyzed these factors in adults, or compared them between healthy controls and patients with patellar injuries, little is known about how these anatomic markers change during skeletal growth and development. Hypothesis/Purpose: (A) The anatomic risk factors associated with patellar instability and dislocation change significantly during skeletal maturation. (B) These age-related changes during maturation will differ between male and female patients. Methods: After institutional review board approval, magnetic resonance imaging data from 239 unique knees (patient age 7-18; 55% female), without previous or current injury, were randomly selected and used to measure patellar height, lateral patellar tilt angle, trochlear width, trochlear depth, trochlear sulcus angle, and tibial tubercle trochlear groove distance. Linear regression was used to test the associations between age and anatomic measurement indices. Subsequently, patients were divided into four age groups: pre-pubertal school-aged children (7-10 years old), early adolescents (11-14 years old), and late adolescents (15-18 years old). Additionally, two-way analysis of variance with the Holm-Sidak post hoc test was used to compare anatomic morphologies between male and female patients in each age group. Results: Patellar height (Caton-Deschamps index), lateral patellar tilt angle and trochlear sulcus angle all decreased significantly with age (P<0.001). Trochlear width, depth, and tibial tubercule trochlear groove distance all increased significantly with age (P<0.001). Except for trochlear width in late adolescence (P<0.001) where males had wider trochlea (medial and lateral) compared to matched females, the age-related anatomic changes were similar between males and females (P>0.1). Conclusion: The findings partially support our hypothesis, as we observed significant age-related changes in all quantified anatomical indices, which was not different (except trochlear width in late adolescence) between males and females. The lack of significant differences in key morphological features of the patellofemoral joint that are linked to patellar dislocation between females and males is consistent with a similar prevalence of this injury between the two. However, the findings suggest that there are significant differences in the trochlear width between females and males at later stages of growth and maturation. The current observations suggest that these anatomic risk factors undergo significant changes during skeletal growth, providing us with a window of opportunity to use prophylactic interventions to prevent or minimize the development of high-risk morphology. Figure 1.1. CDI: Caton-Deschamps Index; TD: Trochlear Depth; TSA: Trochlear Sulcus Angle; LPTA: Lateral Patellar Tilt Angle TTTG: Tibial Tubercle Trochlear Groove Distance. Figure 1.2. Age- and sex-dependent changes in patellofemoral joint morphology during skeletal growth and maturation. Data are presented as mean and SEM (* P<0.05).